Early-onset neonatal sepsis in a Chinese maternal and child healthcare centre, 2017–2023 - Wang, Weilin; Wang, Zhenhui; Wang, Linghua; Li, Suping; Liu, Jiangling; Huang, Yaqin; Liu, Jun; Zhu, Chun; Zhang, Juan; Li, Cairong; Yang, Chunjia; Chen, Qiong; et al. (Frontiers in Pediatrics, 2025)
ObjectiveEarly-onset sepsis (EOS) remains an important issue in neonatal units. Characteristics of EOS from China have not been fully revealed yet. Our aim is to investigate epidemiology, microbiology and clinical feature of EOS in a Chinese maternal and child healthcare centre.MethodsThis is a retrospective observational study of EOS infants born in or admitted to Hunan Provincial Maternal and Child Health Care Hospital from January 1, 2017 to December 31, 2023.ResultsDuring the study period, there were 131 neonatal infections. The incidence of EOS was 1.12 (95% CI 0.94–1.33) per 1,000 live births or 3.85 (95% CI 3.22–4.56) per 1,000 admissions. Coagulase-negative staphylococci (CoNS) (n = 43, 32.3%), group B Streptococcus (GBS) (n = 24, 18.0%) and Escherichia coli (n = 18, 13.5%) were the predominant pathogens. GBS screening test was performed before delivery in 77.7% mothers of all infants with EOS, and 12.9% of screening results were positive. Among the main pathogens causing EOS, 86% of CoNS strains were resistant to penicillin, while all GBS strains were susceptible to penicillin.ConclusionsWe report a high burden of EOS among infants in the maternal and child healthcare centre from China. CoNS was the most frequent pathogen causing EOS. Longitudinal epidemiologic surveillance is required to improve empiric antibiotic treatment of EOS.